Usage Control of Programs and Application Libraries in z/OS Environment in the Big Data Age [Case of the z/AUDIT product] - Reis, Everson Andrade dos [UNESP]; Brito, Lessiclebes Silva; Chen, J.; Cuzzocrea, A.; Yang, L. T. (Ieee, 2013)
The great volume of information is currently a reality. Processing these data, mainly in institutions with a great capacity of processing, is carried out by means of mainframes that are capable of performing operations at a great speed and on an extremely large volume of data in the Big Data age. Indirect methods of gauging the usage of software installed in the mainframe environment are used to measure the usage of products, making it difficult to obtain information to renew these products. This paper presents the z/Audit product, which offers information on the actual usage of the programs installed in the mainframe environment. The product features data extration for mining (data mining) and for presentation (analytics) of this information with open-source products.
Keywords: z/OS Environment; Data Mining; Information Analysis